Role of GABA on Growth, Yield Contributing Characters and Yield of Sesame - Zubair, Hasan Muhammad; Islam, Md. Mothaharul; Rahman, Md. Shahidur; Islam, Mohammad Mahbub; Islam, Md. Shariful; Rahman, Mohammad Mustafizur (International Journal of Bio-resource and Stress Management, 2010)
The experiment was carried out to investigate the effect of GABA on growth, yield attributes and yield of a popular sesame cultivar BARI Til-2. The experiment comprised of five levels of GABA, viz. 2, 3, 4, 5 and 6 mg l-1, and distilled water as control. Result revealed that leaf dry weight, stem dry weight, root dry weight, TDM, CGR, RGR, number of flower bud, number of capsule, number of seeds capsule-1 and seed yield being the highest in 5 mg l-1 concentration over those in control. Moreover, GABA had no significant influence on capsule length, capsule diameter and 1000-seed weight. Application of GABA at 5 mg l-1 as foliar spray could be the suitable concentration for enhancing growth, yield attributes and yield of sesame.